A systematic review of oil tanker truck disasters: Identifying prevention targets. Issue 4 (June 2019) - Ewbank, Clifton; Gupta, Shailvi; Stewart, Barclay T.; Kushner, Adam L.; Charles, Anthony
Graphical abstract: Highlights: Oil tanker disasters cause considerable morbidity and mortality worldwide. "Scooping, " or oil poaching was responsible for 28% of injuries and 45% of deaths. Using a Haddon matrix, actionable targets for global prevention were identified. Abstract: Introduction: Oil tanker truck disasters have been reported worldwide; however, the circumstances, causes, and health effects of these disasters have not been described. To address this gap, we performed a systematic review using PRISMA criteria to better understand this public health problem and identify prevention targets. Methods: The academic and lay literatures were systematically searched for terms related to oil tanker truck disasters. Reports about civilian oil tanker truck disasters that occurred from 1997–2017 were included. Details about the disasters were summarized, including circumstances, identifiable causes, and health effects. Results: The search yielded 4713 Nexis Uni articles, 199 Google results, and one PubMed article; 951 records met inclusion criteria, describing 224 oil tanker truck explosions or fires. At least 2909 people died as a result of these disasters, and 3038 additional people were hospitalized. Almost all deaths (94%) occurred in low- and low-middle-income countries (LMIC). This may largely be due to scooping – the practice of collecting spilled oil from disabled tanker trucks for use or resale. Using the Haddon matrix, potential targets for future disaster prevention were identified. Conclusions: These data highlight the circumstances, causes, and health burden related to oil tanker truck disasters. Most began as collisions or rollovers, but nearly half of the fatalities involved scooping. The findings suggest opportunities to promote road safety, improve scene safety and security protocols used by drivers and first responders, and promote public understanding of the dangers of scooping to prevent mass casualty disasters from disabled tanker trucks, particularly in LMIC.